Plasma amino acid profiles of dogs with the hepatocutaneous syndrome and dogs with other chronic liver diseases - Rommaneeya Leela‐arporn; Karah Burns DeMarle; Cailin R. Heinze; Cynthia R. L. Webster (Journal of Veterinary Internal Medicine, 2025)
Abstract Background Dogs with hepatocutaneous syndrome (HCS) have marked plasma hypoaminoacidemia, but its occurrence in dogs with chronic liver diseases not associated with HCS (non‐HCS CLD) is unknown. Objectives To determine if plasma hypoaminoacidemia occurs in dogs with non‐HCS CLD, compare plasma amino acid (PAA) profiles between dogs with non‐HCS CLD and HCS, and define a sensitive and specific PAA pattern for diagnosing HCS. Animals Data were collected from client‐owned dogs, a prospective cohort of 32 with CLD and 1 with HCS, and a retrospective cohort of 7 with HCS. Methods Prospective study. Dogs with chronic serum liver enzyme increases were recruited after hepatic biopsy. Plasma amino acid profiles were measured using high‐performance liquid chromatography. Plasma amino acid concentrations were compared between dogs with non‐HCS CLD and HCS. Regression analysis was performed to identify a unique PAA pattern for HCS diagnosis. Results Twelve dogs each with vacuolar hepatopathy or chronic hepatitis and 8 dogs with congenital disorders (primary hypoplasia of the portal vein or ductal plate malformations) were enrolled. Compared to non‐HCS CLD dogs, HCS dogs had significantly lower plasma concentrations of several amino acids. Regression analysis revealed that glutamine, glycine, citrulline, arginine, and proline concentrations less than 30% of the mean reference value had 100% sensitivity, specificity for diagnosing HCS. Conclusions and Clinical Importance Generalized plasma hypoaminoacidemia does not accompany non‐HCS CLD. Concentrations of 5 specific amino acids less than 30% of the mean reference value can serve as a noninvasive biomarker for diagnosing HCS.